The procedures for the collection of urine samples and arrest with regards to drug cases in Malaysia - Md Said, Muhamad Helmi; Asokakumar, Anusha; Bong, Jia Er; Biamin, Nurul Arwani Zafirah; A Rahim, Muhammad Khabir Hariz; Mohd Alam Shah, Nurin Athirah; Azman, Awathif (UUM Press, 2022)
This research focuses on the position of the relevant procedures concerning an arrest with regards to drug cases in Malaysia. There are three relevant acts that provide for the procedures for arrest concerning drug related cases in Malaysia. They are the Dangerous Drugs Act 1952 (DDA1952), the Criminal Procedure Code and the Drugs Dependants (Treatment and Rehabilitation) Act 1983 (1983 Act). However, there are conflicts between the application and the interpretation of the relevant provisions under each of these Acts by itself. Hence, this article outlines three objectives ie.: (i) to identify the various provisions relating to drug cases in Malaysia; (ii) to identify and analyse the position and the interpretation of the Malaysian criminal procedure law with regards an arrest concerning drug related cases; and (iii) to suggest improvements that can be made to the law governing an arrest relating to drug cases in Malaysia. In order to achieve these objectives, the research used a qualitative approach with pure legal method as statutes and legal cases would be used as primary source. The research found that that the courts cannot come to a conclusion on whether one or two bottles of urine sample is needed for an examination. This research also found that under the 1983 Act, there have been no recent cases that discussed on the procedures for arrest as well as the number of urine samples that needed to be collected as most of the recent cases were to be tried under the DDA 1952. Finally, there are conflicts in determining the manner of arrest relating to drugs cases under the DDA 1952. Thus, this research suggests an amendment to the Dangerous Drugs Act 1952. The issue of how many bottles of urine samples that need to be collected as well as the issue of whether the MOH Guidelines and IGSO have the relevant force of law must be addressed in this amendment. Next, this research also suggests that the 1983 Act be revised as well as updated due to the arising issues as mentioned earlier.